The Power of Research and Stakeholder Collaboration in Enhancing Early Childhood Care and Education in Low- and Middle-Income Countries - Nirmala Rao; Caroline Cohrssen; Manya Bala (MDPI AG, 2024)
The early years of a child's life are crucial in laying the foundations of learning and development that shape life trajectories [...]